Preventing Terrorism by Strengthening Community Based Ecosystem in Bali Province (Department of International Relations, Universitas Brawijaya, 2022)
Bali Bomb on 2002 becomes the first and the entry point of terrorism issues in Indonesia. It has devastated more than 200 people lives and damage the overall image of Bali as the paradise site in the world and Indonesia as a secure state. Since then, the local government try to protect the potential of terrorist attack. With its indigenous, the local government not only optimizing its agencies but also build a cooperation with the local structure of governance which has built before Indonesia exist. This paper seeks to analysis the collaboration works of these actors to maintain the stability and secure condition in Bali, especially from the terrorism issue. The research conducted through qualitative method, using interview keys person as the main references and official documents, journals, articles, databases as the supporting resources. By using the concept of the role of concentric circle of society in preventing terrorism, this research found that there is systematic communication and coordination between the government agencies and local communities in preventing the terrorism action. And by having a periodic, continuous communications, coordination, and build a controlling mechanism, amongst local government agencies such as Kesbangpol, FKPT, Babinsa, RT/RW staffs, and local actors such as Village Structure of Pakraman, Pecalang, and FKUB, they can create almost a comprehensive ecosystem to protect Bali island from the threat so far. Since 2005 there is no terrorism activity detected in this Island. Another interesting finding from this ecosystem is that this local wisdom system so far does not bring any resistance from the society and trust building among them are getting stronger.